Characterization of native and denatured ricin using MALDI-TOF/MS - Sehgal, P.; Rao, M. K.; Kumar, O.; Vijayaraghavan, R. (Cellular and Molecular Biology, 2010)
Ricin is a toxic protein present in the seeds of castor bean plant. It can be inactivated by heat; therefore characterization of denatured ricin is essential to differentiate it from native ricin and to avoid any ambiguity in its identification. In this study, potential of mass spectrometry using MALDI-TOF/MS has been exploited to investigate the effects of heat treatment on ricin and spiked food matrices. The molecular weights of ricin, ricin A (A1 and A2) and B chain were found to be 62.8 kDa, 31.2 kDa, 32.5 kDa and 32 kDa respectively. The mass spectrum revealed a polypeptide chain of 11.1 kDa for denatured ricin. The peptide mass fingerprinting showed 24 peptides, six were common both in native and denatured ricin. The differentiating peptide at position 294-318 (m/z 934.533) was observed only in denatured ricin. The three selected marker peptides m/z 1013.6, 1310.7, 1728.9 are chosen for identification of ricin inactivated by heat in spiked apple juice and milk samples by immunocapture analysis. There is always a probability of denatured non- toxic ricin being confused with native (toxic) ricin to create unnecessary panic. Keeping this probability in mind, our study will be of immense value in minimising such risk.